ANALISIS KESULITAN GURU MADRASAH IBTIDAIYAH DALAM PENILAIAN PEMBELAJARAN TEMATIK KURIKULUM 2013 - Dian Eka Lestari; Zahrotul Luthfiyah (CENDEKIA, 2019)
This study aims to explain and analyze the difficulties of teachers in carrying out the 2013 thematic learning assessment curriculum, the factors that cause teachers' difficulties in carrying out the 2013 thematic learning assessment curriculum and the efforts that MI teachers can do to overcome the difficulties in evaluating the 2013 thematic learning curriculum in MIM Kendalkemlagi. This type of research is a case study research with a qualitative approach. Data collection methods used were interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation and conclusion drawing. The technique of determining the validity and validity of data uses triangulation of techniques and sources. The results of this study indicate that the difficulties experienced by MI teachers in carrying out the 2013 curriculum thematic learning assessment include the preparation of an assessment format and assessment instruments; understand children with a variety of material from several content subjects combined in one theme; understanding questions to students who are still not fluent in reading; KI and KD mapping process, assessment process, learning process, and determining the assessment tools used. Efforts made by the teacher to overcome these difficulties are by attending the 2013 curriculum training, communicating and consulting a lot of parties both the school principal, vice curriculum or peers or other teachers.